Mudanças alimentares na coorte NutriNet Brasil durante a pandemia de covid-19 - Steele, Eurídice Martínez; Rauber, Fernanda; Costa, Caroline dos Santos; Leite, Maria Alvim; Gabe, Kamila Tiemann; Louzada, Maria Laura da Costa; Levy, Renata Bertazzi; Monteiro, Carlos Augusto (Revista de Saúde Pública, 2020)
OBJECTIVE To describe the dietary characteristics of participants in the NutriNet Brasil cohort immediately before and during the covid-19 pandemic. METHODS Our data stem from an adult cohort created to prospectively investigate the relationship between diet and morbidity and mortality from chronic non-communicable diseases in Brazil. For this study, we selected the first participants (n = 10,116) who answered twice to a simplified questionnaire on their diet the day before, the first time when entering the study, between January 26 and February 15, 2020, and the second between May 10 and 19, 2020. The questionnaire inquiries about the consumption of healthy (vegetables, fruits and legumes) and unhealthy (ultra-processed foods) eating markers. Comparisons of indicators based on the consumption of these markers before and during the pandemic are presented for the study population and according to gender, age group, macro-region of residence and schooling. Chi-square tests and t-tests were used to compare proportions and means, respectively, adopting p < 0.05 to identify significant differences. RESULTS For all participants, we found a modest but statistically significant increase in the consumption of healthy eating markers and stability in the consumption of unhealthy food markers. This favorable pattern of dietary changes during the pandemic occurred in most sociodemographic strata. We observed a less favorable changing pattern, with a tendency to increasing consumption of healthy and unhealthy food markers, in the Northeast and North macro-regions and among people with less schooling, suggesting social inequalities in the response to the pandemic. CONCLUSIONS If confirmed, the trend of increased consumption of ultra-processed foods in underdeveloped regions and by people with less schooling is concerning, as eating these foods increases the risk of obesity, hypertension and diabetes, whose presence increases the severity and lethality of covid-19.